2005
DOI: 10.28945/811
|View full text |Cite
|
Sign up to set email alerts
|

Using Technology-Mediated Learning Environment to Overcome Social and Cultural Limitations in Higher Education

Abstract: Adoption of Internet-based communication and learning technologies could overcome the limitations caused by the social and cultural values of a society. Zayed University (ZU) is a femaleonly university in a modern Arab country that holds dear its high appreciation to cultural and social values. This paper explores the impact and effectiveness of the outcome-based technologymediated learning environment for the College of Information systems (CIS) students. This environment compliments the classroom activities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 1 publication
3
8
0
Order By: Relevance
“…More than 70% of the participants working in Libya spent (2-5) hours per day using the Internet, while more than 45% of the participants based in the UK spent (6-9) hours per day. These results assert the findings of [1], [11], and [13]. The style of education system in Libya, based on traditional ways of teaching, might affect the participants' usage of the Internet.…”
Section: Teaching Timesupporting
confidence: 80%
See 2 more Smart Citations
“…More than 70% of the participants working in Libya spent (2-5) hours per day using the Internet, while more than 45% of the participants based in the UK spent (6-9) hours per day. These results assert the findings of [1], [11], and [13]. The style of education system in Libya, based on traditional ways of teaching, might affect the participants' usage of the Internet.…”
Section: Teaching Timesupporting
confidence: 80%
“…Thus, it appeared that the time spent using technology for teaching per week was inadequate, comparing this result with the time spent in teaching per week. This result confirms the need to implement an active learning approach [13].…”
Section: Time Spent Using Technology In Teachingsupporting
confidence: 74%
See 1 more Smart Citation
“…As Lubna asserted, ICTs cannot be used in the UAE as they are in the West simply because UAE nationals want to use them in the frame of their own culture and traditions. An example of a cultural issue that was consistent in both the literature and the findings from this research was the lack of face-to-face communication in the new computer era as discussed above (Al Omoush et al, 2012;Bhatti et al, 2005).…”
Section: The Electronic Journal Of Information Systems In Developing supporting
confidence: 65%
“…Learners developed a more favorable attitude toward learning when they experienced blended (or hybrid, or mixed-mode) learning, a combination of actual class time and online learning, where they were allowed a certain amount of control over when, where, and how they learned [24]. Bhatti, Tubaisahat, and El-Quawasmeh [25] found that the less learners depended on the teachers' help, the more satisfied they felt with blended learning. Previous studies were conducted to compare the learning motivation in two teaching approaches, and the findings revealed that the blended approach produced more active learning and motivation comparing to the traditional approach [26,27,28] Aforesaid benefits of the blended learning concept strengthened my beliefs and confidence in creating a blended learning model for oral skill development to be used in an English course.…”
Section: Motivation In Learningmentioning
confidence: 99%